A study of bladder dysfunction in women with type 2 diabetes mellitus - Ritu Karoli; Sanjay Bhat; Jalees Fatima; S Priya (Indian Journal of Endocrinology and Metabolism, 2014)
Introduction: Diabetes mellitus has been associated with an earlier onset and increased severity of urologic diseases that often result in debilitating urologic complications. Diabetic bladder dysfunction refers to a group of bladder symptoms occurring in patients with diabetes mellitus ranging from bladder over activity to impaired bladder contractility. Aim: Bladder dysfunction is an under evaluated issue in women with diabetes. Aim of our study was to investigate prevalence of bladder dysfunction and its relation with other chronic complications of diabetes in women with type 2 diabetes. Materials and Methods: In a hospital-based cross sectional study, a cohort of women with type 2 diabetes mellitus who had lower urinary tract symptoms (LUTS) were enrolled. We used the American Urological Association Symptom Index (AUA-SI) to assess the severity of LUTS and the Indevus Urgency Severity Scale (IUSS) to assess presence of overactive bladder (OAB). Age-BMI- matched controls that did not have diabetes but had lower urinary tract symptoms were also studied and compared with women with type 2 diabetes. Urodynamic evaluation was done in willing patients. Results: LUTS attributable to bladder dysfunction were reported in 67% of women with type 2 diabetes after exclusion of other causes. Out of them, 36% had moderate to severe LUTS (total AUA-SI score >7). Prevalence of OAB was 53%. Urodynamic evaluation revealed presence of stress urinary incontinence in 48% patients and changes of detrusor over activity and detrusor under activity in 23% and 11% patients, respectively. Among the chronic complications of diabetes, peripheral neuropathy, nephropathy, and presence of metabolic syndrome were significantly associated with moderate to severe LUTS and OAB. Conclusion: Bladder dysfunction is a highly prevalent complication in women with diabetes. Chronic complications of diabetes especially neuropathy, nephropathy, and presence of metabolic syndrome are important predictors of bladder dysfunction.